Using waste polymers as a reliable alternative for asphalt binder modification – Performance and morphological assessment - Costa, L. M. B. (2019)
The use of plastic wastes as an alternative to virgin polymers can be a remarkable environmentally friendly idea for road paving construction or rehabilitation. Therefore, this study aimed at assessing the potential benefits of modifying a conventional 35/50 penetration grade bitumen, with uncontaminated waste polymers (ethylene vinyl acetate and high-density polyethylene) carefully selected from plastic recycling plants. A virgin polymer (styrene-butadienestyrene) was also used as reference material since it is the polymer most commonly used for bitumen modification. The performance (physical, storage stability, and rheological properties) and morphologic characteristics of the different waste polymer modified binders were thoroughly evaluated and compared with those of the 35/50 bitumen and the virgin polymer modified binder. It was concluded that recycled EVA and virgin SBS modified binders could perform similarly, namely regarding their viscosity and rheological properties. Furthermore, EVA modified binder presented slightly better storage stability probably due to its homogeneous dispersion. The recycled HDPE modified bitumen reveals some promising physical properties (associated with rutting resistance), but it presents the worst resilience and creep recovery. The outcome of this work is the development of new asphalt binders modified with waste polymers as reliable alternatives for road paving activities due to their excellent performance, comparable to that obtained with the most commonly used virgin polymer.